Simulation tool for MRPC telescopes of EEE experiment. Issue 1 (1st November 2022) - Mandaglio, G.; Abbrescia, M.; Avanzini, C.; Baldini, L.; Ferroli, R. Baldini; Batignani, G.; Battaglieri, M.; Boi, S.; Bossini, E.; Carnesecchi, F.; Cicalò, C.; Cifarelli, L.; et al.
Abstract : The Extreme Energy Events (EEE) experiment consists in a network of cosmic muon tracker telescopes, each made of three Multi-gap Resistive Plate Chambers (MRPC), able to precisely measure the absolute muon crossing time and the muon integrated angular flux at the ground level. To investigate the MRPC telescope response and performance, a simulation tool was developed in GEMC, software package based on GEANT4 libraries. The framework was validated by comparing simulations with the EEE experimental data. Detailed description of telescope response is fundamental to carry on the physics program of the EEE project, and it could open other research avenues, such as using the telescope in combination with other detectors to perform a (muon) tomography of material surrounding the telescope. In this paper, the EEE simulation framework will be presented reporting results and discussing further applications.